2011
DOI: 10.1080/09064710.2010.513691
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and drought affect yield response of bell pepper similarly

Abstract: There is a growing realization that an increasing number of countries are approaching full utilization of their conventional water resources and that the quantity of good-quality water supplies available to agriculture is diminishing. Effects of irrigation regime and irrigation water salinity on bell pepper including yield, fruit number and quality, vegetative and root growth, evapotranspiration and water use efficiency were investigated in this study by conducting two different experiments. Six different sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 11 publications
(9 reference statements)
1
34
2
5
Order By: Relevance
“…Pepper is one of the most important crops in Mediterranean area, which is usually classified as a salt-sensitive species (Kurunc et al, 2011;del Amor and Cuadra-Crespo, 2011), even though Aktas et al (2006) observed that salt tolerance can vary amongst pepper genotypes. A promising perspective to improve pepper resistance to salinity is the use of grafting of commercial cultivars onto salt-tolerant rootstocks (Penella et al, 2013;Penella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pepper is one of the most important crops in Mediterranean area, which is usually classified as a salt-sensitive species (Kurunc et al, 2011;del Amor and Cuadra-Crespo, 2011), even though Aktas et al (2006) observed that salt tolerance can vary amongst pepper genotypes. A promising perspective to improve pepper resistance to salinity is the use of grafting of commercial cultivars onto salt-tolerant rootstocks (Penella et al, 2013;Penella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pepper is one of the most important vegetable crops in these areas and is considered sensitive to salinity [3], even though salt tolerance can vary between pepper genotypes [4]. Some pepper accessions have been identified as salinity-tolerant and have been successfully used as pepper rootstocks under saline conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Letey & Dinar (1986) stated that different conditions for evapotranspiration were obtained by applying different soil moisture regimes but rarely by using saline water. Ozturk et al (2004) reported decreasing effect of salinity on water consumption for lemon balm, Yurtseven et al (2005) for tomato, Ünlükara et al (2008) for okra, Düzdemir et al (2009) for cowpea, Ünlükara et al (2010) for eggplant, Kurunc et al (2011) for bell pepper. Plant water consumption also changes with changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%